Effect of graphene oxide dosage on the deterioration properties of cement pastes exposed to an intense nitric acid environment. (1st February 2021) - Muthu, Murugan; Ukrainczyk, Neven; Koenders, Eddie
Highlights: Graphene oxide inclusion in cement matrix reduced the considered porosity to 48% by acting as crack-arrestor. Addition of 0.03 wt% GO increased the quantity of portlandite in cement matrix to 4.9%. Resistance and Young's modulus of cement paste against nitric acid attack improved with an increasing GO dosage. Mass loss in 0.03 wt% GO-modified cement specimen after HCl attack is 17% lesser than the control mix (i.e., without any GO). GO inclusion did not influence the mineralogical composition of cement matrix altered by the nitric acid attack. Abstract: In this study, the effect of graphene oxide (GO) dosage on the performance of cement pastes against an extreme nitric acid environment was investigated. A significant volume of cement matrix was affected because of such attack. The loss in specimen mass and sectional area before and after acid attacks were compared to validate the relative performance between the cement mixes. Compared to the 28-day cured reference mix, the mass and sectional area losses in the acid exposed cement specimen had reduced up to 17% and 25% when the matrix was modified using 0.03 wt% GO, respectively. With an increase in GO dosage from 0 to 0.03 wt% at an interval of 0.01 wt%, it was found that the porosity of cement pastes significantly declined due to crack-arresting effects, which also explained the improved resistance of cement composites against the acidic medium. The GO presence did not influence the mineralogy of the altered cement matrix. Still, it contributed to the material stiffness, which was determined after conducting multiple characterisation studies. Thus, the GO-modified cement concrete was found to be a promising material to construct the storage structures operating under aggressive chemicals and crack inducing conditions.